ANTIOXIDANT ACTIVITY TEST OF AFRICAN LEAVES PURIFICATION EXTRACT (Vernonia amygdalina Del) WITH DPPH METHOD - Nina Karlina; Aan Kunaedi; Didin Ahidin; Uzlifatul Jannah; Yasmin Zahiyah (Universitas Muhammadiyah Magelang, 2023)
African leaves (Vernonia amygdalina Del) is a plant that can be used as a medicinal plant because it contains flavonoid compounds that are effective as natural antioxidants that can suppress free radicals. The purpose of this study was to determine the antioxidant activity of the purified extract of Vernonia amygdalina Del. Antioxidant activity test of purified extract of Vernonia amygdalina Del leaves against 1,1-diphenyl-2-picrylhydrazil (DPPH) was measured with a UV-Vis spectrophotometer at a wavelength of 516nm using Vitamin C as a comparison. The results of the non-specific parameters of Vernonia amygdalina Del leaf Simplicia were drying shrinkage of 0.79±0.02%; water content of 7.33±2.08%; water-soluble essence content of 20.5±1.73 %; and ethanol of 14.5±4.35 %. The results of purified extract screening of Vernonia amygdalina Del leaves, contained chemical compounds, namely the class of flavonoid compounds, tannin compounds, steroid compounds, and saponin compounds. Testing for flavonoids using the Thin Layer Chromatography method on the purified extract contained two spots with Rf values of 0.68 and 0.5 while in quercetin there was one spot with an Rf value of 0.68, thus the purified extract of Vernonia amygdalina Del leaves contained flavonoids. Vernonia amygdalina Del leaf purified extract has a very strong antioxidant activity with an IC50 value of 13.54±0.10 µg/mL. The results showed that the purified extract of Vernonia amygdalina Del leaves had very strong antioxidant activity.